Targeting Kaposi’s sarcoma associated herpesvirus encoded protease (ORF17) by a lysophosphatidic acid molecule for treating KSHV associated diseases - Rafeeq, Misbahuddin M; Habib, Alaa Hamed; Nahhas, Alaa F.; Binothman, Najat; Aljadani, Majidah; Almulhim, Jawaher; Sain, Ziaullah M; Alam, Mohammad Zubair; Alturki, Norah A; Alam, Qamre; Manish, Manish; Singh, Rajnish Kumar (Frontiers in Cell and Developmental Biology, 2023)
Kaposi’s sarcoma associated herpesvirus (KSHV) is causative agent of Kaposi’s sarcoma, Multicentric Castleman Disease and Pleural effusion lymphoma. KSHV-encoded ORF17 encodes a protease which cleaves -Ala-Ala-, -Ala-Ser- or -Ala-Thr-bonds. The protease plays an important role in assembly and maturation of new infective virions. In the present study, we investigated expression pattern of KSHV-encoded protease during physiologically allowed as well as chemically induced reactivation condition. The results showed a direct and proportionate relationship between ORF17 expression with reactivation time. We employed virtual screening on a large database of natural products to identify an inhibitor of ORF17 for its plausible targeting and restricting Kaposi’s sarcoma associated herpesvirus assembly/maturation. A library of 307,814 compounds of biological origin (A total 481,799 structures) has been used as a screen library. 1-oleoyl-2-hydroxy-sn-glycero-3-phospho-(1′-myo-inositol) was highly effective against ORF17 in in-vitro experiments. The screened compound was tested for the cytotoxic effect and potential for inhibiting Kaposi’s sarcoma associated herpesvirus production upon induced reactivation by hypoxia, TPA and butyric acid. Treatment of reactivated KSHV-positive cells with 1-oleoyl-2-hydroxy-sn-glycero-3-phospho-(1′-myo-inositol) resulted in significant reduction in the production of Kaposi’s sarcoma associated herpesvirus. The study identified a lysophosphatidic acid molecule for alternate strategy to inhibit KSHV-encoded protease and target Kaposi’s sarcoma associated herpesvirus associated malignancies.